Severity of gambling behaviors: exploring associations with venues, legality, and substance use - Hagit Bonny-Noach (BMC, 2024)
Abstract Introduction The COVID-19 pandemic has been linked to an increase in gambling behaviors, potentially leading to Gambling Disorder (GD) and adverse health and social consequences. Problematic gambling has received little research attention over the years in Israeli society and the issue of gambling is not high on the list of priorities of Israeli policymakers. The present study examined gambling behavior in Israel on a continuum of severity and its association with venues where the gambling occurs, legality, attitude toward the legalization of casinos and poker, and substance use. Methods The study questionnaires were distributed to approximately 15,000 Jewish-Israeli adults via internet panel. From 3,088 Israeli adults who answered the questionnaire, 1,251 (40.5%) reported gambling in the last year and were included in the analyses. Results Based on the Problem Gambling Severity Index, 60% of participants were classified as non-problem gamblers, 25% as at low-risk for a gambling problem, 11% as at moderate risk, and 4% as having a gambling problem. Most online gambling was practiced by non-problem gamblers (40%) and most illegal gambling was by low-risk gamblers (34%). The more severe the gambling behavior was on the continuum, the more it was associated with illegal substance use and positive attitudes toward legalized casinos in Israel. Logistic regression showed the odds of developing moderate and problem gambling were 3.8 times higher for online gamblers (OR = 3.8; CI 2.6-5.4; p < 0.000) and 3.3 times higher for illegal gamblers (OR = 3.3; CI 2.2-4.9; p < 0.000). Conclusion Though more research attention should be paid to gambling behaviors, harm reduction gambling interventions should be made available to all categories on the continuum of severity of gambling behaviors. The present study provides evidence-based information to promote health policies that aim to prevent and reduce harm for Israeli gamblers.